2008
DOI: 10.1016/j.juro.2008.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Results of Bilateral Nerve Sparing Laparoscopic Retroperitoneal Lymph Node Dissection for Testicular Cancer

Abstract: Bilateral nerve sparing laparoscopic retroperitoneal lymph node dissection is feasible and associated with low morbidity if performed by experienced hands. The oncological efficacy of this approach is promising and currently under evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 18 publications
2
37
2
1
Order By: Relevance
“…35 The surgery was successfully finished in all 19 of their patients and no conversion was necessary, and there was no recurrence after a mean follow-up of 17.2 months. Another study compared the unilateral template with a bilateral template in PC-RLA.…”
Section: Technique Templatementioning
confidence: 83%
“…35 The surgery was successfully finished in all 19 of their patients and no conversion was necessary, and there was no recurrence after a mean follow-up of 17.2 months. Another study compared the unilateral template with a bilateral template in PC-RLA.…”
Section: Technique Templatementioning
confidence: 83%
“…Given the high potential for complications in post-chemotherapy patients, LRPLND should only be attempted in highly selected patients by surgeons with significant laparoscopic experience. [Steiner et al 2008]. The authors found teratoma, necrosis/fibrosis, and active tumor in 4, 14 and 1 patient respectively.…”
Section: Lrplnd Techniquementioning
confidence: 95%
“…In most contemporary series adjuvant chemotherapy continues to be given to patients with any nodal involvement at the time of LRPLND. Of the 122 node positive patients reported in the series listed in Table 1 following LRPLND [Skolarus et al 2008 [Steiner et al 2008]. None of the five patients were given adjuvant chemotherapy and all are without recurrence at follow-up intervals of 2-35 months.…”
Section: Lrplnd Techniquementioning
confidence: 99%
“…The use of laparoscopy in postchemotherapy RPLND appears technically feasible but uncertain with regards to its long-term outcome [51,52]. Most of the current experience is in the primary setting as opposed to after chemotherapy.…”
Section: Laparoscopymentioning
confidence: 99%